Nutrition and Feeding of Organic Pigs - Blair, Robert (CAB International, 2017)
This second edition has been completely updated, addressing how to formulate organic diets as well as the feasibility of using novel feedstuffs and their acceptability by consumers. It includes international standards of organic feeding, feed-related disease in organic herds, and producers' experiences of appropriate breeds and production systems.